Innovative Learning: Utilizing Card Sort Media to Amplify Arabic Vocabulary Understanding in NW Lenek Junior High School - Hady, Rosli; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2023)
This study aims to explore the effectiveness of using Card Sort media in improving Arabic vocabulary comprehension at NW Lenek Junior High School. The research method employed was an experiment with a pre-test and post-test design involving two groups of students. Data collection techniques were conducted through vocabulary tests before and after the intervention using Card Sort media. Data analysis was performed by comparing pre-test and post-test scores between the experimental and control groups. The results showed a significant improvement in Arabic vocabulary comprehension among the experimental group that used Card Sort media compared to the control group that did not. The implication of this study is that the use of Card Sort media can be an effective tool in enhancing Arabic vocabulary comprehension at NW Lenek Junior High School. By implementing this innovative learning approach, it is hoped to make a positive contribution to Arabic language learning at the school and improve overall student academic achievement.